The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/ijcs.12522
|View full text |Cite
|
Sign up to set email alerts
|

Repeated payment delinquency among young adults in the United States

Abstract: There is concern in the United States about young adults falling behind financially due to the increased use of student loans and low wages. This study investigates payment delinquency as a measure of financial distress to better understand how young adults might be struggling. Personality traits are incorporated into the model to determine the extent to which behavioural factors are correlated with financial behaviors and if they predict a habit trend of payment delinquency. The 1997 National Longitudinal Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…It can be understood as the chronic tendency to attach value to saving money in a consistent manner and explains such beneficial financial behaviors as an increased ability to delay gratification, less discounting of future gains and higher savings levels (Dholakia et al, 2016). The positive habit formation which is central to a strong personal savings orientation helps prevent problematic financial behaviors such as payment delinquency (Letkiewicz and Heckman, 2019), which is one of the risk factors of financial vulnerability (Hoffmann and McNair, 2019). Individuals' personal savings orientation also has a positive relationship with their expected future financial security (Ponchio et al, 2019).…”
Section: Personal Savings Orientationmentioning
confidence: 99%
“…It can be understood as the chronic tendency to attach value to saving money in a consistent manner and explains such beneficial financial behaviors as an increased ability to delay gratification, less discounting of future gains and higher savings levels (Dholakia et al, 2016). The positive habit formation which is central to a strong personal savings orientation helps prevent problematic financial behaviors such as payment delinquency (Letkiewicz and Heckman, 2019), which is one of the risk factors of financial vulnerability (Hoffmann and McNair, 2019). Individuals' personal savings orientation also has a positive relationship with their expected future financial security (Ponchio et al, 2019).…”
Section: Personal Savings Orientationmentioning
confidence: 99%
“…Among major personality factors, the one most often associated with debt is conscientiousness—or, rather, a lack of it. For example, Letkiewicz and Heckman (2018, 2019) found that more conscientious people were less likely to default on student loans; they were even less likely to take out a mortgage. Similarly, in an investigation of the relation between personality and financial well‐being, Donnelly et al.…”
Section: The Psychology Of Getting Into Debtmentioning
confidence: 99%
“…All debt is not created equal. The consequences of being late or defaulting on unsecured debt like credit card loan differ significantly from those resulting from default on secured debt like home mortgage (Letkiewicz & Heckman, 2019). Defaulting on a mortgage loan can result in home foreclosure.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%